Assessing thermochemical properties of materials through ab initio quantum-mechanical methods: the case of α-Al2O3. Issue 17 (7th May 2015) - Erba, Alessandro; Maul, Jefferson; Demichelis, Raffaella; Dovesi, Roberto
<x xml:space="preserve">Abstract</x> Accurate ab initio calculations of thermodynamic and structural thermal properties of corundum demonstrate its quasi-harmonic nature up to the melting temperature.